UNCERTAINTIES ON LEAD ISOTOPE ANALYSES:DECONVOLUTION IN THE DOUBLE-SPIKE METHOD - Powell R.; Woodhead J.; Hergt J. (My University, 1998)
A weighted least-squares method is used to generate the `true' lead isotopic composition from measurements on unspiked and spiked aliquots of a sample using the double-spike method. A form for the weighting based on theoretical mass spectrometer errors is used.The least-squares approach is more reliable for this deconvolution of lead isotopic compositions than current methods, and allows uncertainties and correlations on the true isotopic composition to be estimated, a feature of importance in many applications. The approach allows the prediction of run parameters for `optimum' spike analysis.
Keywords: PB ISOTOPES; TECHNIQUES; STATISTICS